BrowserVox: Uma Extensão De Interface De Voz Para Um Navegador Open-Source - Munzlinger, Elizabete; Soares, Fabricio da Silva; Forster, Carlos Henrique Q. (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2010)
The use of voice in computational systems interfaces have been utilized for many users who can enjoy the voice to communicate. The performance of current voice technologies and the business demand to improve usability and accessibility in their products and services has been increasing the use of voice interaction in multimodal interface (MMI) applications [11]. This paper presents the previous work improvement [6] through a Voice Interface (VUI) extension for Mozilla Firefox Web Browser. The BrowserVox extension is a plugin with improvements, where some problems of paper [6] was solved. During BrowserVox developement arose project questions about interface and interaction. This questions are described in this paper.